Towards internationally competitive regions in Ukraine: critical assessment - Daria Zvirgzde; Javier Revilla Diez (European Regional Science Association (ERSA), 2012)
Globalisation as a dominant tendency of the XXI century has initiated the rise of the scale and dynamics of economic interactions on the international, national and regional levels. Regions have started to compete as the sources of economic growth since the disproportional levels of their development led to the escalation of the disparities on the global economic platform. Experience of the most successful and highly developed states clearly shows that the growth of the competitive economy on the macro-level is only possible through the accumulation of the regional economic potentials on the meso-level. The notion of international regional competitiveness has been paid attention to in economic and regional science literature, but still there is no one single definition of what a competitive region means. The paper presents the author's own definition of an internationally competitive regional economy as the starting point of the assessment of the scientific and innovative potentials of the regions of Ukraine, their link to the regional competitiveness of the Ukrainian economy and its regional attractiveness towards FDI. Analysis of the impact of FDI on the local business, of whether MNCs do add value to the local regional growth, situating the regional competitive advantage, of the level of embeddedness of MNCs into regional innovation systems as the primary sources of regional competitiveness is introduced in the paper within the methodology framework of the survey carried out in three regions of Ukraine within the SEARCH Project of the Seventh Framework Programme. Formulation of strategic policies targeting at raising the level of the regional competitiveness stands as a coherent discussion focus after cluster models of boosting the levels of international competitiveness with the means of increasing the level of productivity and economic connectivity are proposed. The paper aims at, firstly, the assessment of the theoretical aspects and up-to-date methodologies of the analysis of the international competitiveness of the regions; secondly, at identification of the system of determinants of the level of international competitiveness of the regions within the conditions of globalisation; thirdly, at the study of the economic potential of the regions of Ukraine as one of the drivers of regional competitiveness; and fourthly, the paper will come up with the strategic ways of accumulation of the innovative competitiveness of the regions of Ukraine.
Keywords: 330